Thermoplastic forming of bulk metallic glass—Applications for MEMS and microstructure fabrication - Schroers, Jan; Nguyen, Tranquoc; O’Keeffe, Sean; Desai, Amish (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2007)
Thermoplastic forming of bulk metallic glass (BMG) is introduced as a fabrication method for micro-electromechanical systems and microstructure. Forming of the BMG takes place in the supercooled liquid region, where the BMG exists as a highly viscous metastable liquid. In this temperature region the BMG can be formed very similar to plastics under comparable forming pressure and temperatures. This technology allows precise replication of small features with a homogeneous material, free of stresses and porosity. Our processing method includes a hot-cutting technique that enables separation of the parts from the BMG reservoir and leaves a flat plane. It also allows creating net-shapes three-dimensional parts on the microns scale. In order to quantify the formability a simple flow law is applied which was also used to estimate the minimum feature size this technology is capable to replicate.